UJI AKTIVITAS FAGOSITOSIS MAKROFAG KOMBINASI EKSTRAK ETANOL HERBA MENIRAN (Phyllanthus niruri L.), DAUN SIRIH MERAH (Piper crocatum Ruiz. & Pav.), DAN UMBI KELADI TIKUS (Typhonium flagelliforme (Lodd.) Blume) SECARA IN VITRO - , LISTYA DIFITA, Dr. Agustinus Yuswanto, S.U., Apt. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Recently, the high level of pollution and uncertain weathers change cause the decrease in body defense. Meniran herb (Phyllanthus niruri L.), Sirih merah leaf (Piper crocatum Ruiz. & Pav.), and Keladi tikus tuber (Typhonium flagelliforme (Lodd.) Blume) have been widely used as immunomodulator agent by improving the immune system. The combinations of those three are expected to provide a synergistic effect through non-specific immune system by the increase in macrophage phagocytic activity parameter. Samples of Phyllanthus niruri L. herb, Piper crocatum Ruiz. & Pav. leaves, and Typhonium flagelliforme (Lodd.) Blume) tuber in the crude form are obtained from PT. Gama Herbal Indonesia. The samples are ground and macerated with ethanol 70% in solvent ratio (1:7). Extracts are consist of ekstrak etanol meniran (EEM), ekstrak etanol sirih merah (ESM) dan ekstrak etanol keladi tikus (EKT) made in 1 Î¼g/ml, 10 Î¼g/ml, and 100 Î¼g/ml concentrations with the composition of each combinations are combination 1 (EEM 28,6%, ESM 14,3%, EKT 57,1%), combination 2 (EEM 30,8%, ESM 7,7%, EKT 61,5%), combination 3 (18.2% EEM, ESM 9.1%, 72.7% EKT), and combination 4 (30% EEM, ESM 30%, EKT 40%). The test of macrophage phagocytic ability use latex beads as trigger is compared by media control and DMSO 0,05% v/v control. The results of the phagocytic capacity and phagocytic index parameters were analyzed with one-way ANOVA in 95% reliability level for variable concentrations of 1 Î¼g/ml, 10 Î¼g/ml, and 100 Î¼g/ml. The combination of variables was analyzed with non-parametric test Kruskall-Wallis continued by Mann-Whitney in 95% reliability level because the ANOVA assumptions were not met. The results showed that all groups of combination in 1 Î¼g/ml, 10 Î¼g/ml, and 100 Î¼g/ml concentrations were able to increase the phagocytic activities compared to the control with optimum concentration of 10 Î¼g / ml.